2024
DOI: 10.1007/s10238-023-01280-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of bone turnover markers and DXA parameters to predict bone metastasis progression during zoledronate treatment: a single-center experience

Stella D’Oronzo,
Mauro Cives,
Eleonora Lauricella
et al.

Abstract: Bone metastases (BM) are a serious cancer complication, potentially causing substantial morbidity. Among the clinical issues related to BM, there is the lack of specific tools for early diagnosis and prognosis. We explored whether combining bone turnover markers (BTM) with dual-energy X-ray absorptiometry (DXA) assessment could identify early BM progression and risk of skeletal-related events (SREs) during zoledronate treatment. Before the initiation of zoledronate (T0) and after six months of treatment (T1), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 53 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…An interesting aspect, which is suggested by these findings, is the potential of BTMs to stratify patients at a high risk of (bone) metastatic disease and govern further treatments in the adjuvant setting to increase bone-metastasis-free survival; a comprehensive list of biomarkers is provided by Wang et al [ 28 ]. Interestingly, stronger evidence of this notion has arisen in the context of advanced disease [ 29 , 30 , 31 ]. D’Oronzo and colleagues recently studied 47 patients with bone metastatic BC who underwent BTM measurements and dual-energy X-ray absorptiometry (DXA) before bisphosphonate treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An interesting aspect, which is suggested by these findings, is the potential of BTMs to stratify patients at a high risk of (bone) metastatic disease and govern further treatments in the adjuvant setting to increase bone-metastasis-free survival; a comprehensive list of biomarkers is provided by Wang et al [ 28 ]. Interestingly, stronger evidence of this notion has arisen in the context of advanced disease [ 29 , 30 , 31 ]. D’Oronzo and colleagues recently studied 47 patients with bone metastatic BC who underwent BTM measurements and dual-energy X-ray absorptiometry (DXA) before bisphosphonate treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The authors showed that OPG levels < 5.2 pmol/L were associated with an increased risk of progression. Skeletal-related events were also significantly associated with lower concentrations of osteocalcin, OPG, lower lumbar T-Score, and femur bone mineral density at baseline [ 30 ]. Another prospective study of patients with bone metastases (various tumors including BC) by Ibrahim et al demonstrated that RANKL transcription levels were the best marker of the response of bone metastases during treatment with zoledronic acid [ 31 ].…”
Section: Discussionmentioning
confidence: 99%